THE ROLE OF E-COMMERCE IN BUSINESS DEVELOPMENT IN MSMEs IN THE EAST MEDAN REGION - Ananda, Runi; Fitri, Ridatul; Azwabi, Hariz Madani; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine the role of e-commerce in business development in MSMEs in the East Medan region. The research approach used is a qualitative approach. The data sources used are through observation and interviews, descriptive data analysis techniques. Respondents in the research were conducted by conducting interviews with MSME owners in the East Medan District. The results of this research show that the role of e-commerce for MSMEs, it is able to increase MSME business income with ease of digital transactions, making it easier for consumers to make transactions, making it easier to market business products and being able to expand market access . Obstacles in implementing e-commerce on the security of personal information data of MSMEs.